Samuel Johnson and the culture of property - Hart, Kevin 1954- (Cambridge University Press, 1999)
Kevin Hart traces the vast literary legacy and reputation of Samuel Johnson. Through detailed analyses of the biographers, critics and epigones who carefully crafted and preserved Johnson's life for posterity, Hart explores the emergence of what came to be called 'The Age of Johnson'. Hart shows how late seventeenth- and early eighteenth-century Britain experienced the emergence and consolidation of a rich and diverse culture of property. In dedicating himself to Johnson's death, Hart argues, James Boswell turned his friend into a monument, a piece of public property. Through subtle analyses of copyright, forgery and heritage in eighteenth-century life, this study traces the emergence of competing forms of cultural property: a Hanoverian politics of property engages a Jacobite politics of land. Kevin Hart places Samuel Johnson within this rich cultural context, demonstrating how Johnson came to occupy a place at the heart of the English literary canon